2022
DOI: 10.3389/fpubh.2022.958270
|View full text |Cite
|
Sign up to set email alerts
|

Compliance level toward COVID-19 preventive measures and associated factors among the Ambo University community, 2021

Abstract: BackgroundThe coronavirus illness is a highly contagious viral infection with serious health consequences that has occurred all around the world. Application of COVID-19 prevention precautions and social interventions by the general public are critical to successfully combating the epidemic. Therefore, this study aimed to determine the level of compliance and associated factors with COVID-19 prevention strategies.MethodsA facility based cross-sectional study was conducted from June 01 to August 30, 2021 on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…For example, Rogers, Bahr, & Benjamin [ 36 ] found that higher education levels were associated with more favorable attitudes towards the influenza vaccine. Additionally, Roga, Bekele & Gonfa [ 37 ] reported that higher education levels were associated with greater compliance with COVID−19 prevention measures. Therefore, the current study’s finding that education level did not predict attitudes toward infectious diseases in university students suggests that other factors may be more influential in shaping attitudes in this population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rogers, Bahr, & Benjamin [ 36 ] found that higher education levels were associated with more favorable attitudes towards the influenza vaccine. Additionally, Roga, Bekele & Gonfa [ 37 ] reported that higher education levels were associated with greater compliance with COVID−19 prevention measures. Therefore, the current study’s finding that education level did not predict attitudes toward infectious diseases in university students suggests that other factors may be more influential in shaping attitudes in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this was not the case in Yemen, where little effort was put into spreading awareness. For example, although the Yemeni Supreme National Emergency Committee for Covid-19 had an official account on Twitter and a WhatsApp group, where they routinely share cases and death reports [ 35 ], none of our informants were aware of its existence or have seen their reports. This reflects that those reports were also poorly promoted and not widely published; in addition, Twitter is the less used social media platform in Yemen.…”
Section: Discussionmentioning
confidence: 99%
“…Sikap dan perilaku yang dimanifestasikan dalam bentuk keyakinan efikasi (keyakinan akan prinsip yang mendatangkan hasil yang diharapkan) merupakan faktor praktis yang signifikan dan paling berpengaruh serta mampu memediasi hubungan antara pengetahuan dengan protokol kesehatan memakai masker, mencuci tangan dan menghindari keramaian (Lee et al, 2021). Sebagaimana telah dilaporkan dalam studi Roga et al (2022), bahwa meningkatkan kepatuhan protokol kesehatan COVID-19 sebagai bentuk upaya pencegahannya untuk menjadi lebih baik adalah akibat faktor pengetahuan yang baik sebesar 2,6 kali, faktor sikap yang positif sebesar 4,5 kali dan akibat faktor perilaku yang baik yaitu sebesar 2,9 kali.…”
Section: Gambaran Sikap Dan Perilaku Dengan Kepatuhan Protokol Covid-19unclassified